ANALYSIS OF HALAL CERTIFICATES POST THE ISSUE OF LAW NUMBER 33 OF 2014 CONCERNING HALAL PRODUCT GUARANTEES RESEARCH STUDY OF MEDAN CITY - Sardi; Henry Aspan; Tamaulina Br Sembiring (PT. Radja Intercontinental Publishing, 2024)
A significant step in regulating halal certification in Indonesia occurred with the enactment of Law no. 33 of 2014 concerning Halal Product Guarantees. This law replaces previous regulations and establishes a more comprehensive legal framework to regulate the halal certification process. With this law, it is hoped that a solid foundation can be created to maintain the certainty and quality of halal products in the domestic research market This discuss about How Arrangement About Hal Certificates in Indonesia?, What Factors That Become Inhibitor In Making Or Publishing Halal Certificate ? How Implementation To Post Halal Certification Constitution Number 33 of 2014 Concerning Guarantee Halal Products ? Through approach qualitative with studies case as method main , research This identify change authority and structure institutions , potential contradictions and domination of the Halal Inspection Institute (LPH), as well as governance and infrastructure challenges​ in implementation halal certification . The research results show the unclear role of LPH, potential conflicts of authority, and obstacles in governance and infrastructure. To overcome this obstacle, the proposed solution involves clarifying the role of LPH, close collaboration between relevant institutions, establishing clear guidelines and standards, improving infrastructure and human resources, active involvement of related parties, updating and harmonizing policies, and improving monitoring and evaluation systems. This research emphasizes the importance of regulatory updates, involvement of related parties, and harmonization with international standards to increase efficiency and fairness in the halal certification system.